Antitumor effect of afatinib, as a human epidermal growth factor receptor 2‐targeted therapy, in lung cancers harboring HER2 oncogene alterations. Issue 1 (3rd December 2015) - Suzawa, Ken; Toyooka, Shinichi; Sakaguchi, Masakiyo; Morita, Mizuki; Yamamoto, Hiromasa; Tomida, Shuta; Ohtsuka, Tomoaki; Watanabe, Mototsugu; Hashida, Shinsuke; Maki, Yuho; Soh, Junichi; Asano, Hiroaki; et al.
Abstract : Human epidermal growth factor receptor 2 (HER2) is a member of the HER family of proteins containing four receptor tyrosine kinases. It plays an important role in the pathogenesis of certain human cancers. In non‐small‐cell lung cancer (NSCLC), HER2 amplification or mutations have been reported. However, little is known about the benefit of HER2‐targeted therapy for NSCLCs harboring HER2 alterations. In this study, we investigated the antitumor effect of afatinib, an irreversible epidermal growth factor receptor (EGFR)–HER2 dual inhibitor, in lung cancers harboring HER2 oncogene alterations, including novel HER2 mutations in the transmembrane domain, which we recently identified. Normal bronchial epithelial cells, BEAS‐2B, ectopically overexpressing wild‐type HER2 or mutants (A775insYVMA, G776VC, G776LC, P780insGSP, V659E, and G660D) showed constitutive autophosphorylation of HER2 and activation of downstream signaling. They were sensitive to afatinib, but insensitive to gefitinib. Furthermore, we examined the antitumor activity of afatinib and gefitinib in several NSCLC cell lines, and investigated the association between their genetic alterations and sensitivity to afatinib treatment. In HER2 ‐altered NSCLC cells (H2170, Calu‐3, and H1781), afatinib downregulated the phosphorylation of HER2 and EGFR as well as their downstream signaling, and induced an antiproliferative effect through G1 arrest and apoptotic cell death. In contrast, HER2 ‐ or EGFR ‐non‐dependent NSCLC cells were insensitive to afatinib. In addition, these effects were confirmed in vivo by using a xenograft mouse model of HER2 ‐altered lung cancer cells. Our results suggest that afatinib is a therapeutic option as a HER2‐targeted therapy for NSCLC harboring HER2 amplification or mutations. Abstract : In this study, we demonstrated the antitumor effect of afatinib, as a HER2‐targeted therapy, in lung cancers harboring HER2 alterations in vitro and in vivo . Our results strongly suggest that afatinib is a promising therapeutic option for NSCLC patients with HER2‐amplification or mutations.